(3OQGSI GdSdhc GdGfSGfj GdaQOj h GdLeGYj aj efXeGJ GdGYeGds - (3eMeO bGSe(B, (3GdbQjhJjs ((3YeGf(B:s (3OGQ hGFd(B,s, 2009)
(3eGgjI GdSdhc GdJfXjej, GdOhGaY (B: (3Gdeaghe h GdfXQjGJ , GdTNUjI (B: (3Gdeaghe h GdfXQjGJ , YedjI GdGOQGc , GdLeGYGJ h JCKjQgG Ydi GdSdhc GdJfXjej , GdefGN GdJfXjej h GdKbJaI GdJfXjejI h Gdbje h GdGJLGgGJ , GdbjGOI GdGOGQjI , YedjI GdGJUGdGJ GdGOGQjI , EOGQI GdUQGYGJ , GOGQI GdJhJQ I VZhW GdYed , GOGQI GdGHOGY h GdGHJcGQ aj GdGOGQI , GOGQI GdJZjjQ h GdJWhjQ , GdYhGed GdJfXjejI h CKQgG Ydi GdSdhc GdJfXjej , eTGcd GdYGedjf aj GdJfXjeGJ GdeYGUQI , HYV GdGfeGW GdJfXjejI dJfXjeGJ GdeSJbHd (B.s
(3eQGLY (B:(3dcd aUd eQLYs
Keywords: (3EOGQI GdCYeGds; (3GdSdhc GdEfSGfjs; (3GdSdhc GdJfXjejs